Literary Myths in Mixed Reality - Vassiliadi, Martha; Sylaiou, Stella; Papagiannakis, George (Frontiers in Digital Humanities, 2018)
It is well known that the Decadent movement in European literature (fin de siècle) depends on the narrative of the antiquity, as it is revealed from the discoveries of archaeology in the second half of the 19th century. Amid the ruins of the past authors, painters and poets re-conceptualize time and history through a modernist vision based on an imaginary reconfiguration of the antiquity. In this context, the myth of a city (Pompeii) or of a woman (Salomé) offer examples, which would illustrate in a great variety the synergy of a multi-temporal and multi-cultural memory of the myth. In this paper we identify a "content-based" shortcoming of modern Mixed Reality (MR) intangible and tangible digital heritage storytelling applications for digital humanities. It is an important problem as the very nature of these applications is often been identified with either misguided storytelling, or non-compelling, non-engaging narratives, except the initial captivating moments due to the immersive 3D visual simulation. We propose a new concept that forthcoming MR applications can draw from: "Literature-based MR Presence". Based on modern literature excerpts associated with the real heritage sites, digital narratives can achieve new depths of Presence (phenomenon of behaving and feeling as if we are in the virtual/augmented world created by computerized displays). They would evoke deeper sensations if their dramaturgical plots were based on literary texts associated with the heritage sites, from users, as similar to those often associated with cognitive presence, e.g. when someone is feeling of being transported in an alternate reality when simply reading a compelling novel or poem. We examine modern MR simulations and serious games for digital heritage and propose this conceptual framework to study them under this new concept, in order to achieve heightened feeling of Presence in the virtual heritage simulations, based on recent novel h/w advances. Two cases of a tangible historical place (Pompeii) and an intangible character (Salome) are identified as cultural heritage items, with associated reconstruction examples via Mixed Reality simulations and corresponding early modern literary works.